Microbial therapeutics for canine periodontal disease: current status and future perspectives - Yang, Seok Bin; Moon, Ji-Hoi (Frontiers in Veterinary Science, 2026)
Periodontal disease in dogs arises from ecological disruption of the oral microbiome. Sequencing-based studies and quantitative molecular analyses reveal characteristic dysbiotic transitions in affected dogs, with coordinated increases in Porphyromonas gulae, Prevotella, and Treponema, along with Treponema denticola and Tannerella forsythia, together with a loss of commensal-dominated genera such as Moraxella, Capnocytophaga, and members of the Neisseriaceae family. Rather than being driven by a single dominant pathogen, accumulating evidence indicates that canine periodontitis is driven by polymicrobial synergy within dysbiotic biofilms. This ecological perspective has stimulated growing interest in microbial therapeutics aimed at modulating community structure and function instead of relying solely on broad-spectrum antibiotics. Probiotics and postbiotics show potential in reducing halitosis and modulating epithelial innate immune responses. Bacteriophage-based approaches and predatory bacteria exhibit strain-specific antimicrobial activity in preclinical human or in vitro models, although their relevance to canine oral disease remains unvalidated. Synthetic biology and CRISPR-based antimicrobial systems provide conceptual frameworks for genotype-targeted modulation of virulence. Remaining challenges include transient microbial persistence, limited veterinary clinical evidence, biosafety concerns, and the absence of standardized regulatory pathways. Collectively, emerging microbial therapeutics highlight the potential but also the current limitations of ecology-guided, non-antibiotic strategies for canine periodontal therapy.